2013
DOI: 10.1057/jdhf.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

The procyclicality of hedge fund alpha and beta

Abstract: François-Éric Racicotis Associate Professor of Finance at the Telfer School of Management, University of Ottawa. His research interests focus on the problems of measurement errors, specification errors and endogeneity in financial models of returns. He is also interested in developing new methods used for forecasting financial time series − especially hedge fund risk. He has published several books and many articles in quantitative finance and financial econometrics. Raymond Théoretis Full Professor of Finance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Procyclicality thus seems to decrease in the hedge fund industry, a good news for investors in search for higher yields like pension funds (Racicot and Théoret, 2013). One promising avenue for further research is to model the co-movements of the returns, α's and β's of the hedge fund strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Procyclicality thus seems to decrease in the hedge fund industry, a good news for investors in search for higher yields like pension funds (Racicot and Théoret, 2013). One promising avenue for further research is to model the co-movements of the returns, α's and β's of the hedge fund strategies.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the correlation between factors and/or to their time-varying dimensions. Racicot and Theoret (2013) find that the hedge fund exposure to these factors may change substantially over the business cycle. portions of the probability distribution.…”
Section: Risk Profile Of Hedge Fundsmentioning
confidence: 91%
“…The mentioned study of Racicot and Theoret (2013) showed that the alphas and betas of hedge funds were pro-cyclical, and another study of Ang et al (2011) discussed the counter cyclical behavior of the leverage of hedge funds. According to the study of Ang et al (2011), the hedge fund leverage tended to be predictable by economic factors.…”
Section: Hedge Fund Leverage and Monetary Policymentioning
confidence: 99%
“…In particular, decreases in interest rates and rising market values predict increases in hedge fund leverage. The study of Racicot and Theoret (2013) revealed that the alpha of hedge funds was increasing during upswing cycles on the market. During downturn cycles the alpha is decreasing, which shows that there is a cyclical response of the hedge fund performance.…”
Section: Hedge Fund Leverage and Monetary Policymentioning
confidence: 99%
See 1 more Smart Citation